Perancangan Mesin Pres Sampah Basah Untuk Pembangkit Listrik Tenaga Sampah di Universitas Singaperbangsa Karawang - Willy Rolies; Marno; Kardiman (Jurnal Serambi Engineering, 2024)
Waste-to-energy (WtE) plants in Indonesia present a novel approach to the increasingly urgent challenge of waste management. This research project is concerned with the design of a waste press machine that will be suitable for use with the UNSIKA WtE incinerator. The primary objective is to reduce the volume of waste material entering the incinerator. This process not only enhances combustion efficiency but also contributes to a reduction in emissions and the utilisation of renewable energy. This research entails the selection of suitable materials for the press machine and the design of a mold that aligns with the dimensions of the incinerator hopper. The utilisation of SolidWorks 2023 software facilitates more precise design analysis and simulation. The findings of this research demonstrate that the constructed press machine is effective in reducing waste volume, thereby making a valuable contribution to waste management and the utilisation of renewable energy. In conclusion, this research not only provides a technical solution for waste management but also serves as a reference for further research in the same field.